Developing a Conceptual Experiential Learning–Based School of Entrepreneurship Model to Foster Entrepreneurial Mindset and Character in Senior High School - Dede Jajang Suyaman; M. Januar Ibnu Adham; Amri Dhimas Maulana; Mohamed Saddik; Thaufan Abiyuna; Lia Eka Septi; Elia Nurindah Sari; Zahra Yasifa Hasbullah (IJECA (International Journal of Education and Curriculum Application), 2026)
Entrepreneurship education at the secondary school level is increasingly recognized as a strategic pathway to cultivate future-ready competencies beyond technical business skills. However, many school-based programs remain fragmented, focusing primarily on business projects without systematically integrating dispositional development and institutional support mechanisms. This study aims to develop and conceptually validate the Experiential Learning–Based School of Entrepreneurship (PEIR) model designed to strengthen the entrepreneurial mindset and entrepreneurial character of high school students. The study uses a Research and Development (R&D) approach adapted from Borg and Gall with a focus on the model development stage, including needs analysis, conceptual design, expert validation, and limited testing. Data were collected using a needs assessment questionnaire, expert validation sheets, a model feasibility observation checklist, a student perception questionnaire, and standardized instruments to measure entrepreneurial mindset and entrepreneurial character. The results of the needs analysis showed pedagogical fragmentation, limited institutional integration, and the lack of a dispositional assessment mechanism that explicitly measures the strengthening of entrepreneurial mindset and character. The PEIR (Prepare–Experience–Internalize–Reflect) model was designed as a structured and integrated experiential learning cycle with institutional support and a multidimensional evaluation system. Expert validation results showed a very high level of content validity (S-CVI = 0.96) and excellent instrument reliability (α = 0.93). A limited trial showed a high level of model feasibility (90%), very positive student perceptions (M = 4.28), and moderate improvement based on N-Gain values for the variables of entrepreneurial mindset (0.43) and entrepreneurial character (0.38). These findings indicate that the integration of structured experiential learning within an institutional framework can produce meaningful dispositional reinforcement. Theoretically, this study contributes by integrating cognitive and affective-ethical dimensions into a single operational learning architecture. Practically, the PEIR model offers an adaptive and sustainable framework for schools to institutionalize entrepreneurship education oriented towards character building and entrepreneurial mindset.